Development of the formulation and technology for functional jelly using mulberry syrup - A. I. Blyagoz; M. V. Vlasenko (Новые технологии, 2022)
The use of modern technologies in the production of food products often leads to decrease in nutritional value due to the loss of essential nutrients. In this regard, there is a need to search for new technological solutions in the field of food fortification. Functional food products are one of the actively developing areas for solving this problem. The main component of functional foods are functional ingredients, thanks to which the product exhibits useful, health-improving properties. At present, functional nutrition has become available, that is the ability to make a varied diet from foods rich in proteins, vitamins, flavonoids and other biologically active components. In this aspect, mulberry fruits are promising plant raw material with a high content of biologically active substances. This fact creates an opportunity for their use in the production of functional products. The article presents the developed functional product, namely jelly using mulberry syrup – mulberry doshab. The influence of the dosage of mulberry syrup, as well as the influence of the type and concentration of gelling agents on the quality of jelly have been studied. The optimal ratio of jelly components has been selected. The formulation and technology of jelly has been developed. The organoleptic and physical and chemical indicators of the quality of the finished product have been determined. A significant content of vitamins and minerals in the finished product has been established. The conducted theoretical and experimental studies have confirmed the effectiveness of mulberry syrup, and allowed the development of a new recipe for gelled dessert, the introduction of which contributes to the expansion of the range of functional products.